Performing Language Variation to Promote Sociolinguistic Equality: A Systematic Literature Review - Obispo, Flordeluna L.; Estremera, Michael L. (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Sociolinguistic equality requires improving public understanding of language variation and challenging language ideologies that perpetuate social inequalities. This study introduces a public engagement strategy using research-based verbatim theatre to promote sociolinguistic equality, defined as the respectful treatment of all language users. The verbatim theatre approach, utilizing recorded delivery, is systematically applied to research data of language variation among older adults in Tyneside. The data selection and development of the “From You to Me” production followed a rigorous process that adhered to the PRISMA 2020 framework. The initial data consisted of 50 hours of interview recordings. Participants were pre-selected for social and linguistic diversity. Extracts were selected based on sociolinguistic representativeness, theatrical criteria, and ethical considerations, resulting in the inclusion of data from thirteen participants in the production. Audience evaluations indicate the production’s potential for improving understanding of language variation and shifting attitudes.